Mixed reality simulations for social-emotional learning. (March 2021) - Murphy, Kristin M.; Cook, Amy L.; Fallon, Lindsay M.
Although social-emotional learning is associated with long-term success in school and careers, it is often a missing link in U.S. public education. The COVID-19 pandemic has intensified the need for social-emotional supports for children. In this time of crisis, educators have also sought new ways to make connections and reimagined how students might actively learn with each other. Kristin Murphy, Amy Cook, & Lindsay Fallon discuss what they have learned about using mixed reality simulations to facilitate social-emotional learning with children and what makes this technology a promising active learning tool.